Substructure Development and Deformation Twinning Stimulation through Regulating the Processing Path during Multi‐Axial Forging of Twinning Induced Plasticity Steel. Issue 11 (9th August 2018) - Akbarian, Shima; Zarei‐Hanzaki, Abbas; Abedi, Hamid Reza; Unnikrishnan, Rahul; Moat, Richard
Abstract : Multi‐axial forging (MAF) at room temperature is employed to investigate the effects of deformation processing path and the amount of imposed strain on the deformation mechanisms of a twinning‐induced plasticity (TWIP) steel. The results indicate that the twin frequency is decreased by applying the 2nd compression (∑ ɛ = 0.8), however, an unexpected increase is realized at the end of first MAF pass (∑ ɛ = 1.2). This is attributed to the change in strain path and orientation dependence of deformation twinning. The latter is phenomenal considering the previous researches reporting the suppression of twinning at the early stage of deformation ( ɛ < 0.4). The same sequence is followed during the second pass of MAF process. Interestingly, the progressive and continues substructure development along with dynamic Hall–Petch effect results from deformation twinning leads to an appreciable grain refinement. The latter is accompanied by the sharp drop of hardening rate in corresponding flow curves. The microtexture analysis indicates the strengthened texture of the 1 pass‐processed specimens which is weaken at the end of 2 pass due to the recrystallization and increasing the number of texture component. The current work also explores the room temperature mechanical properties of the multi axial forged workpiece through elaborating the miniaturized tensile testing method. Abstract : The effects of deformation processing path on the deformation mechanisms of a twinning‐induced plasticity (TWIP) steel at room temperature is investigate by Multi‐axial forging (MAF). The activation of deformation twinning along with substructure development even after 2 MAF passes leading to possessing continuous dynamic recrystallization beside twin fragmentation. The micro‐texture analysis is explored regarding deformation and grain refinement mechanisms.